Flow and Satisfaction With Life in Elite Musicians and Top Athletes - Habe, Katarina; Biasutti, Michele; Kajtna, Tanja (Frontiers in Psychology, 2019)
Although flow has been studied extensively in music and sport, there is a lack of research comparing these two domains. With the aim of filling this gap, élite musicians and top athletes in Slovenia were contrasted in the current study. Differences for flow and satisfaction with life between élite musicians and top athletes were explored. Individual versus group performance setting and gender differences were considered. 452 participants; 114 élite Slovenian musicians (mean age 23.46 years) and 338 top Slovenian athletes (mean age 22.40 years) answered questions about flow and satisfaction with life measures. The results show differences between élite musicians and top athletes in four flow dimensions: transformation of time and autotelic experience were higher in musicians while clear goals and unambiguous feedback were higher in athletes. However differences in global flow were not confirmed. Élite musicians and top athletes experienced flow more often in group than in individual performance settings and surprisingly it was experienced more in male than in female top performers. Satisfaction with life has a positive correlation with all nine dimensions of flow, but only challenge-skill balance was a significant predictor for satisfaction with life.